Moulding volksmoeders or volks enemies? Female students at the University of Pretoria, 1920-1970 (Historia, 2021)
One of the key elements that nationalist ideologues have used over the last two centuries as a mobilising force is “a highly stylised symbolic identity of ideal womanhood to which the ordinary women of the nation are meant to conform or at least to aspire” .Women are called upon to be mothers, not only of their private families, but of the “super-family”that is the nation. In Afrikaner nationalism this translated into the image of the volksmoeder.During a time of immense turmoil and change, Afrikaner women had to be, in the words of D.F. Malan, then leader of the National Party in the Cape Province, the constructive force of the nation as “no nation can be built by the sword alone; the trowel must feature too. The woman works with the trowel in a constructive manner,particularly in the social terrain, the terrain of education and health”.After consideringthe genesis of the conceptvolksmoeder and various reflections on it, this article will look at the tertiary education of women, specifically at the University of Pretoria (UP). Firstly, the position of women as defined by Afrikaner nationalism and how it manifested at UP will be discussed. Secondly, it will consider the causes and implications of Afrikaner women’s move away from their designated role and place and whether this shedding of their traditional image lead to the undermining of Afrikaner nationalist ideals.
Keywords: nationalist; Afrikaner nationalism; volksmoeder; D.F. Malan; National Party; Cape Province; University of Pretoria (UP).; 1920-1970